Efficacy and safety of pregabalin in generalised anxiety disorder: A critical review of the literature. (October 2015) - Baldwin, David S; den Boer, Johan A; Lyndon, Gavin; Emir, Birol; Schweizer, Edward; Haswell, Hannah
The aim of this review is to summarise the literature on the efficacy and safety of pregabalin for the treatment of generalised anxiety disorder (GAD). Of 241 literature citations, 13 clinical trials were identified that were specifically designed to evaluate the efficacy and safety of pregabalin in GAD, including 11 randomised double-blind trials and two open-label studies. Pregabalin efficacy has been consistently demonstrated across the licensed dose range of 150–600 mg/day. Efficacy has been reported for pregabalin monotherapy in elderly patients with GAD, patients with severe anxiety, and for adjunctive therapy when added to a selective serotonin reuptake inhibitor or serotonin-norepinephrine reuptake inhibitor in patients who have failed to respond to an initial course of antidepressant therapy. The two most common adverse events with pregabalin are somnolence and dizziness, both of which appear to be dose-related. Pregabalin appears to have a low potential for causing withdrawal symptoms when long-term therapy is discontinued; however, tapering over the course of at least one week is recommended. A review of available evidence indicates that pregabalin is a well-tolerated and consistently effective treatment for GAD, with a unique mechanism of action that makes it a useful addition to the therapeutic armamentarium.